2015
DOI: 10.1039/c5ra08015k
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of conformational changes of the triplet prion fibrils for pH

Abstract: The HET-s prion fibril, which is found in the filamentous fungus Podosporaanserina, exhibits conformational changes due to variations in pH. Here, we explain the effects of changing pH on the conformational changes of fibrils through the fundamental eigenmodes of the fibrils, in particular the torsional and bending modes, using a parameter free elastic network model. In particular, the motion resulting from these fundamental eigenmodes is found to be very similar to the conformational changes stimulated by pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Our recent study [19] reports that the size-dependent elastic properties of prion fibrils provide an insight into their critical size of infectious prion fibrils. In addition, a recent study by Choi et al [28] reports the mechanical and structural characteristics of prion fibrils under different pH conditions with using elastic network model (ENM)-based normal mode analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study [19] reports that the size-dependent elastic properties of prion fibrils provide an insight into their critical size of infectious prion fibrils. In addition, a recent study by Choi et al [28] reports the mechanical and structural characteristics of prion fibrils under different pH conditions with using elastic network model (ENM)-based normal mode analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the β‐amyloid fibrillar structure could be regarded as a continuous beam at a certain amount of length, which enabled us to gain further insight on the structural properties e. g. elastic modulus, bending rigidity, persistence length etc. Furthermore, we discovered in our previous works that these properties of amyloids are related to the dynamics of amyloid backbone structures, and these motions of amyloid backbone structure could be presented with their fundamental vibrational mode shapes ,…”
Section: Resultsmentioning
confidence: 96%
“…The simplest analysis techniques, principle component analysis (PCA) and elastic network model (ENM), are usually utilized for the analysis of essential motion and mechanical features of protein structures. These analysis techniques revealed that amyloid fibril morphology changes and mechanical properties can be analyzed by mechanically induced vibrational characteristics ,. In the basic theory of mechanical vibration, bending, torsional, and axial mode shapes are considered, as they are the fundamental mode shapes that are expressed in a low vibration region.…”
Section: Resultsmentioning
confidence: 99%
“…In the first section, the seeding mechanisms of prions for the homogenous and heterogeneous fibrils are introduced, and the Figure 18. Cumulative overlap between normal modes calculated from pH 2 model and direction vector between pH 2 and pH 3 model [64]. molecular structure differences in the assembly process of amyloid fibrils under environmental conditions are described in the second section.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, left-handed prion fibrils had more local contacts than nonprion fibrils, which are consistent with the results of a previous study analyzing hydrogen bonds. Triplet fibrils were also examined by ENM and NMA [64]. In this study, prion triplet fibrils were compared at pH 2 and 3.…”
Section: Simulation Methodsmentioning
confidence: 99%